Secondary Students’ Stable and Unstable Optics Conceptions Using Contextualized Questions - Chu, Hye-Eun; Treagust, David (Springer, 2013)
This study focuses on elucidating and explaining reasons for the stability of and interrelationships between students’ conceptions about Light Propagation and Visibility of Objects using contextualized questions across 3 years of secondary schooling from Years 7 to 9. In a large-scale quantitative study involving 1,233 Korean students and 1,149 Singaporean students, data were analyzed from responses to the Light Propagation Diagnostic Instrument consisting of four pairs of items, each of which evaluated the same concept in two different problem situations. Findings show that only about 10–45 % of students could apply their conceptions of basic optics in contextualized problem situations giving rise to both stable and unstable alternative conceptions. Students’ understanding of Light Propagation concepts compared with Visibility of Objects concepts was more stable in different problem situations. The concepts of Light Propagation and Visibility of Objects were only moderately correlated. School grade was not a strong predictive variable, but students’ school achievement correlated strongly with their conceptual understanding in optics. The teaching and learning approach and education systems in the two countries may have had some influence on students’ conceptual understanding.